Enhancing endometrial receptivity: the roles of human chorionic gonadotropin in autophagy and apoptosis regulation in endometrial stromal cells - Bin Wang; Mingxia Gao; Ying Yao; Haofei Shen; Hongwei Li; Jingjing Sun; Liyan Wang; Xuehong Zhang (BMC, 2024)
Abstract Inadequate endometrial receptivity often results in embryo implantation failure and miscarriage. Human chorionic gonadotropin (hCG) is a key signaling molecule secreted during early embryonic development, which regulates embryonic maternal interface signaling and promotes embryo implantation. This study aimed to examine the impact of hCG on endometrial receptivity and its underlying mechanisms. An exploratory study was designed, and endometrial samples were obtained from women diagnosed with simple tubal infertility or male factor infertile (n = 12) and recurrent implantation failure (RIF, n = 10). Using reverse transcription-quantitative PCR and western blotting, luteinizing hormone (LH)/hCG receptor (LHCGR) levels and autophagy were detected in the endometrial tissues. Subsequently, primary endometrial stromal cells (ESCs) were isolated from these control groups and treated with hCG to examine the presence of LHCGR and markers of endometrial receptivity (HOXA10, ITGB3, FOXO1, LIF, and L-selectin ligand) and autophagy-related factors (Beclin1, LC3, and P62). The findings revealed that the expressions of receptivity factors, LHCGR, and LC3 were reduced in the endometrial tissues of women with RIF compared with the control group, whereas the expression of P62 was elevated. The administration of hCG to ESCs specifically activated LHCGR, stimulating an increase in the endometrial production of HOXA10, ITGB3, FOXO1, LIF and L-selectin ligands. Furthermore, when ESCs were exposed to 0.1 IU/mL hCG for 72 h, the autophagy factors Beclin1 and LC3 increased within the cells and P62 decreased. Moreover, the apoptotic factor Bax increased and Bcl-2 declined. However, when small interfering RNA was used to knock down LHCGR, hCG was less capable of controlling endometrial receptivity and autophagy molecules in ESCs. In addition, hCG stimulation enhanced the phosphorylation of ERK1/2 and mTOR proteins. These results suggest that women with RIF exhibit lower levels of LHCGR and compromised autophagy function in their endometrial tissues. Thus, hCG/LHCGR could potentially improve endometrial receptivity by modulating autophagy and apoptosis.